Informing Healthcare Alarm Design and Use: A Human Factors Cross-Industry Perspective - Zoe M. Pruitt; Lucy S. Bocknek; Deanna-Nicole C. Busog; Patricia A. Spaar; Arianna P. Milicia; Jessica L. Howe; Ella S. Franklin; Seth Krevat; Rebecca Jones; Raj M. Ratwani (Patient Safety, 2023)
# Background